HUBUNGAN MOTIVASI KERJA DENGAN PERILAKU CARING PERAWAT DI RUANGAN INTERNIS RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2015 - Gabriel Naibaho (STIKes Santa Elisabeth Medan, 2016)
High motivation in a person will encourage them to act properly so that it will affect the productivity of work, conversely, if the nurses are not guided by a strong desire and motivation to work it will have an impact on work satisfaction of the nurses and it reflects a low caring behavior that make the nurses become lazy and in doing their activities of serving and taking care of the patients. Goal:The purpose of this study to analyze the effects of exercise range of motion The objective of this study is to investigate the correlation between work motivation with nurses’ caring behaviors in internist room of Santa Elisabeth Hospital Medan. Methods:This study uses a correlative descriptive research design with cross sectional approach. The technique of sampling was performed by using non-probability technique with convenience sampling, with 51 respondents using questionnaire sheets of work motivation 20 statements and 42 statement of the nurses’ caring behavior. Result:The result of the study shows that work motivation category good is as many as 44 (86.3%) nurses, and category good enough is 7 (13.7%) nurses. The nurses’ caring behavior with good category is 16 (31.4%) nurses, good enough is 35 (68.6%) nurses. Conclusion:Based on spearman’s rho test P value = 0.001 and correlation coefficient = 0.603 it can be concluded that research hypothesis (Ha) is accepted that is there is correlation between work motivation with nurses’ caring beahvior in internis room of Elisabeth Hospital Medan. It is suggested to nurses to improve the knowledge, attitudes and skills especially when carrying out their role as executor of professional nursing actions.